(NpRESTUPLENIE I NAKAZANIE(B: [(NrOMAN(B] /s - (NdOSTOEWSKIJ(B, (NfEDORs ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1983)
(NrOMAN (B"(NpRESTUPLENIE I NAKAZANIE(B" (1866) - (NODNO IZ SAMYH ZAME^ATELXNYH TWORENIJ ^ELOWE^ESKOGO GENIQ(B. (N|TO ROMAN O rOSSII SEREDINY (BXIX (NWEKA(B, (NPEREVIW[EJ \POHU GLUBO^AJ[IH SDWIGOW I NRAWSTWENNYH POTRQSENIJ(B, (NROMAN O GEROE(B, (NWMESTIW[EM W GRUDX SWO@ WSE STRADANIQ(B, (NBOLI I RANY SWOEGO WREMENI(B.rus
rus
Keywords: (NpSIHOLOGI^ESKIJ ROMANs; (NkLASSI^ESKAQ PROZAs; (NkRIMINALXNYJ ROMANs